Hubungan Antara Problematic Internet Use dengan Subjective Well Being Anak dan Remaja - Balqis Andini Putri; Hedi Wahyudi (Jurnal Riset Psikologi, 2022)
Abstract. Children and adolescents during the pandemic experience various kinds of changes. The inability to interact and socialize directly with peers cause them to prefer to browse the internet and social media to relieve boredom and negative feeling. This research is a correlational study with 2,765 children and adolescents as respondents throughout Indonesia. The purpose of this study was to obtain empirical data on how closely the relationship between problematic internet use and the subjective well-being of Indonesian children and adolescents during the COVID-19 pandemic. The measuring instrument used the Problematic Internet Use variable was translated by researcher [1] into Indonesian using (GPIUS2) measuring instrument constructed by [2], While the measuring instrument for Subjective Wellbeing used the measuring (CW-SWBS). The analysis technique of this study uses Spearman's Rank so that it is obtained r = -.077 with p = .000, Namely there is a negative relationship between Problematic Internet Use (PIU) and Subjective Well Being (SWB) with a very weak close relationship. This means that the higher the PIU, the lower the SWB of Indonesian children and adolescents during the COVID-19 pandemic. Abstrak. AAnak-anak dan remaja di masa pandemi mengalami berbagai macam perubahan. Ketidakmampuan untuk berinteraksi dan bersosialisasi secara langsung dengan teman sebaya menyebabkan mereka lebih memilih untuk browsing internet dan media sosial untuk menghilangkan kebosanan dan perasaan negatif. Penelitian ini merupakan penelitian korelasional dengan responden sebanyak 2.765 anak dan remaja di seluruh Indonesia. Tujuan dari penelitian ini adalah untuk mendapatkan data empiris tentang seberapa erat hubungan antara penggunaan internet yang bermasalah dengan kesejahteraan subjektif anak dan remaja Indonesia selama masa pandemi COVID-19. Alat ukur yang digunakan variabel Problematic Internet Use yang diterjemahkan oleh peneliti [1] ke dalam bahasa Indonesia menggunakan alat ukur (GPIUS2) yang dikonstruksi oleh [2], Sedangkan alat ukur untuk Subjective Wellbeing menggunakan alat ukur (CW-SWBS). Teknik analisis penelitian ini menggunakan Spearman's Rank sehingga diperoleh r = -.077 dengan p = .000, Yaitu terdapat hubungan negatif antara Problematic Internet Use (PIU) dengan Subjective Well Being (SWB) dengan erat sangat lemah hubungan. Artinya semakin tinggi PIU maka semakin rendah SWB anak dan remaja Indonesia di masa pandemi COVID-19.